2018
DOI: 10.5194/amt-2017-400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Organic Hydroperoxides and Peroxy Acids Using Atmospheric Pressure Chemical Ionization – Tandem Mass Spectrometry (APCI-MS/MS): Application to Secondary Organic Aerosol

Abstract: Abstract.Molecules with hydroperoxide functional groups are of extreme importance to both the atmospheric and biological 10 chemistry fields. In this work, an analytical method is presented for the identification of organic hydroperoxides and peroxy and peracetic acid), as well as the ROOH formed from the reactions of H 2 O 2 with aldehydes (i.e. acetaldehyde, hexanal, glyoxal and methylglyoxal). This new ROOH detection method was applied to methanol extracts of secondary organic aerosol (SOA) material generat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…By analyzing this model hydroperoxide standard with RPLC/ESI-HR-QTOFMS, we were able to determine how the hydroperoxides ionize and their typical neutral losses produced during MS/MS experiments. As shown in Figure S8 , we found that 1,2-ISOPOOH was not only retained and detected as the [M + NH 4 + ] + ion at mass-to-charge ratio ( m / z ) 136 by the RPLC/ESI-HR-QTOFMS positive ion mode method, but it also produced neutral losses of 35 (i.e., loss of H 2 O + NH 3 ) and 51 (i.e., loss of H 2 O 2 + NH 3 ) during MS/MS experiments, which are consistent with the neutral losses we observed for the proposed structures shown in Table 1 and with a prior study by Zhou et al 62 that used atmospheric pressure chemical ionization-tandem mass spectrometry (APCI-MS/MS) operated in the positive mode.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…By analyzing this model hydroperoxide standard with RPLC/ESI-HR-QTOFMS, we were able to determine how the hydroperoxides ionize and their typical neutral losses produced during MS/MS experiments. As shown in Figure S8 , we found that 1,2-ISOPOOH was not only retained and detected as the [M + NH 4 + ] + ion at mass-to-charge ratio ( m / z ) 136 by the RPLC/ESI-HR-QTOFMS positive ion mode method, but it also produced neutral losses of 35 (i.e., loss of H 2 O + NH 3 ) and 51 (i.e., loss of H 2 O 2 + NH 3 ) during MS/MS experiments, which are consistent with the neutral losses we observed for the proposed structures shown in Table 1 and with a prior study by Zhou et al 62 that used atmospheric pressure chemical ionization-tandem mass spectrometry (APCI-MS/MS) operated in the positive mode.…”
Section: Resultssupporting
confidence: 90%
“…Taken together, these observations suggest that compounds other than pinonic acid, pinic acid, and MBTCA that are present in α-pinene ozonolysis SOA induce cellular toxicity. On the basis of previous studies, including work from our group on complementary systems, 54 , 59 the most likely candidate compounds are multifunctional organic peroxides that are generated from α-pinene ozonolysis. Many prior studies have measured a significant organic peroxide contribution to SOA generated from α-pinene ozonolysis, 31 , 57 including multifunctional organic peroxides.…”
Section: Discussionmentioning
confidence: 99%
“…Its molecular formula, C 15 H 22 O 3 , with five degrees of unsaturation, was determined based on the high-resolution electrospray ionization mass spectrometry (HRESIMS) ion peak at m / z 251.1643 [M + H] + (calculated for C 15 H 23 O 3 + , 251.1642). The ion peak at m / z 217.1598 [M + H − H 2 O 2 ] + [ 22 , 23 ] and neutral loss of 51 Da (H 2 O 2 + NH 3 ) from the ammonium adduct, m / z 268.1872 [M + NH 4 ] + [ 24 ] are characteristic evidence for the presence of the hydroperoxy group. The 1 H-NMR spectrum of 1 showed three olefinic protons ( δ H 5.90 (dt, J = 2.9, 1.3 Hz, 1H), 5.37 (t, J = 1.3 Hz, 1H), 5.21 (brs, 1H)), one methine ( δ H 2.37 (m, 1H)), four methylenes ( δ H 2.41 (m, 1H)/1.54 (m, 1H), 2.30 (dd, J = 16.2, 1.3 Hz, 1H)/ 2.14 (dd, J = 16.2, 1.3 Hz, 1H), 2.19 (m, 1H)/1.78 (td, J = 14.1, 4.1 Hz, 1H), 1.53 (m, 1H)/1.42 (td, J = 13.9, 4.1 Hz, 1H), and three methyls ( δ H 0.96 (brs, 3H), 1.93 (t, J = 1.3 Hz, 3H), 1.84 (brs, 3H)).…”
Section: Resultsmentioning
confidence: 99%